Analysis of Hospital Management Information System (SIMRS) in Purwokerto Islamic Hospital - Dion Romodon; Arga Rahardian (Nusantara Science and Technology Proceedings, 2022)
Purwokerto Islamic Hospital is an Advanced Referral Health Facility that receives referrals from first-level health facilities so the hospital management system will become a very important requirement for managers, clinicians, and patients and their families. Hospital Management Information System is a system used to collect management data from a hospital, in which many installations, departments, and units are incorporated into a complete system. The Ministry of Health seven years ago has launched 7 Health Development Reforms, namely 1) revitalization of health services, 2) availability, distribution, retention, and quality of human resources, 3) seeking availability, distribution, safety, quality, effectiveness, affordability of drugs, vaccines and medical equipment, 4) Health insurance, 5) partiality to disadvantaged areas, borders and islands (DTPK) and health problem areas (DBK), 6) bureaucratic reform and 7) world-class health care. Currently, the hospital management information system in the hospital unit needs an operator to operate it. So that managerial and clinicians in accessing information systems in hospitals are also still limited. So the researchers tried to assess the application of a special hospital management information system in intensive care to explore further the advantages and disadvantages or the benefits and obstacles as well as the quality of this hospital management information system. Especially since the implementation until now SIMRS has never been evaluated. From the search results, researchers found many studies on SIMRS. After trying to sort it out, seven studies on SIMRS were taken, starting from the 2005 study to the 2018 study. Most of them used qualitative methods, there was one study in Uganda that used Mixed Methods and two studies that used quantitative (Greece and Kenya). Most of the data collection was in the form of observation and interviews, except for Greece and Kenya with questionnaires and scales, and Uganda which used both questionnaires and interviews. The results of these seven studies show that SIMRS is beneficial from various points of view. General Purpose, To analyze the application of the hospital management information system application program in the intensive care unit of RSI Purwokerto. The specific objective is to find out the benefits or improvement of service quality, the obstacles and the quality of the application program of the hospital management information system of RSI Purwokerto as well as the flow of systems and service procedures in the unit.